Linguistic Characteristics of Feature-Story Headlines in Native English Newspapers and Magazines - Luyen, Nguyen Thi Kim (VNU Journal of Foreign Studies; Vol 32 No 4, 2016)
Abstract: Headlines are often among the most vital parts of every newspaper and magazines as they play a key role in attracting readers’ attention, especially headlines of news stories and feature stories which are the two kinds of headlines focusing on information and discussion respectively. This paper aims to investigate linguistic features of English feature-story headlines in terms of general characteristics, structure, word choice and stylistic devices. By using both qualitative and quantitative methods, the paper has found several features of English feature-story headlines, which have been discussed to provide a deeper insight into the prominent characteristics of English feature-story headlines. This in turns helps enhance readers’ comprehensive skills when they deal with this kind of headlines in English newspapers and magazines. Keywords: Feature-story headlines, linguistic characteristics, headlines, word choice, stylistic devices.